A Review on the Morphology, Cultivation, Identification, Phytochemistry, and Pharmacology of Kitagawia praeruptora (Dunn) Pimenov - Qi Wang; Lulu Ding; Ruihong Wang; Zongsuo Liang (Molecules, 2023)
Kitagawia praeruptora (Dunn) Pimenov, commonly known as Qianhu in China, is a widely used folk Chinese herbal medicine. This article reviews its botanical traits, ethnopharmacology, cultivation techniques, identification, phytochemical compositions, and pharmacological effects. Over 70 coumarin compounds, including simple coumarins, pyranocoumarins, and furanocoumarins, have been isolated within this plant. Additionally, K. praeruptora contains other components such as flavonoids, fatty acids, benzoic acids, and sterols. This information highlights the importance of utilizing active ingredients and excavating pharmacological effects. With its remarkable versatility, K. praeruptora exhibits a wide range of pharmacological effects. It has been found to possess expectorant and bronchodilator properties, cardiovascular protection, antimicrobial and antioxidant activities, anti-tumor effects, and even antidiabetic properties. It is recommended to focus on the development of new drugs that leverage the active ingredients of K. praeruptora and explore its potential for new clinical applications and holistic utilization.